Effects of anion complexation on the photoreactivity of bisureido- and bisthioureido-substituted dibenzobarrelene derivatives - Ihmels, Heiko; Luo, Jia (Beilstein Journal of Organic Chemistry, 2011)
Bisureido- and a bisthioureido-substituted dibenzobarrelene derivative were synthesized and the photoreactivity of two representative examples were studied. Direct irradiation of the ureido-substituted derivative induces a di-π-methane rearrangement to the corresponding dibenzosemibullvalene derivative, whereas the thioureido-substituted derivative is almost photoinert. Complexes of the latter derivative with chloride, carboxylates, or sulfonate anions, however, are efficiently transformed to the dibenzosemibullvalene product upon irradiation, presumably by suppressing the self-quenching of the thiourea units in the complex. The association of the ureido-substituted dibenzobarrelene derivative with (S)-mandelate and irradiation of this complex led to the formation of the dibenzosemibullvalene with moderate stereoselectivity (68:32 er). In contrast, the thioureido derivative showed no such effect upon complexation of chiral anions.
Keywords: dibenzobarrelenes; dibenzosemibullvalenes; di-π-methane rearrangement; supramolecular photochemistry; (thio)urea derivatives